Superconductivity at 3.1 K in the orthorhombic ternary silicide ScRuSi. (14th December 2016) - Ruan, Bin-Bin; Wang, Xiao-Chuan; Yu, Jia; Pan, Bo-Jin; Mu, Qing-Ge; Liu, Tong; Chen, Gen-Fu; Ren, Zhi-An
Abstract: We report the synthesis, crystal structure, superconductivity and physical property characterizations of the ternary equiatomic compound ScRuSi. Polycrystalline samples of ScRuSi were prepared by an arc-melting method. The as-prepared samples were identified as the orthorhombic Co2 P-type o -ScRuSi by powder x-ray diffraction analysis. Electrical resistivity measurements show o -ScRuSi to be a metal which superconducts below a T c of 3.1 K; the upper critical field μ 0 H c2 (0) is estimated to be 0.87 T. The magnetization and specific heat measurements confirm the bulk type-II superconductivity in o -ScRuSi, with a specific heat jump within the BCS weak coupling limit. o -ScRuSi is the first Co2 P-type superconductor to contain scandium. After annealing at 1273 K for a week, o -ScRuSi transforms into hexagonal Fe2 P-type h -ScRuSi, which is a Pauli-paramagnetic metal with no superconductivity observed above 1.8 K.